Three new species of the genus Nitela Latreille, 1809 (Hymenoptera: Crabronidae) from India - Mawadda, N.v. Ayisha; Aseeb, A.k.; Kumar, P. Girish (Zootaxa, 2025)
The genus Nitela Latreille from India is studied and three new species are described, namely, N. pseudocollaris Mawadda & Girish Kumar, N. neoapoensis Mawadda & Girish Kumar, and N. nasseri Mawadda & Girish Kumar, whereas N. domestica Williams, 1928, is a new record for India. An updated key of Oriental Nitela is provided.